Benson’s Relaxation for Fatigue Patient with Coronary Artery Disease - Muliantino, Mulyanti Roberto; Tuti Herawati; Masfuri (Talenta Publisher, 2020)
Fatigue is the major symptoms in patients with coronary artery disease, during recovery period after cardiac events and during cardiac rehabilitation. Benson’s relaxation is one of relaxation as modalities therapy to reduce fatigue, however few studies related to this technique in planned intervention. This study was to measure the effectiveness of Benson’s relaxation in fatigue of coronary artery disease patients during cardiac rehabilitation. It was a quasi-experimental pretest posttest control group design. This study included 29 respondents in Dr.M. Djamil Hospital were assigned to intervention group which receiving Benson’s relaxation technique (n=15) and control group with routine care (n=14). Benson’s relaxation technique was administered for 5 days 2 times a day, each 20 minutes to intervention group. Fatigue was measured using Maastricht Questionnaire (MQ). The result indicated significant reduction in mean of fatigue between intervention and control group (p value < 0,001). The study concluded that Benson’s relaxation technique is an effective non-pharmacological intervention to reduce fatigue in coronary artery disease patients. Keywords: Benson’s relaxation; fatigue; coronary artery disease